Boycotting Israeli Products in the Digital Age: The Influence of Social Media on Consumer Attitudes - Raditya Pratama Putra; Maya Amalia Oesman Palapah; Indri Rachmawati; Ratri Rizki Kusumalestari; Maman Chatamalah (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
Abstract. Amid escalating Israeli attacks on Palestine, widely regarded as war crimes due to the high number of civilian casualties, including children, several nations, including Indonesia, have responded by initiating boycotts of Israeli products. In solidarity with Palestine, the Indonesian Ulema Council (MUI) issued a fatwa urging the public to boycott Israeli products and those supporting them. This move has sparked significant public debate and discussion, particularly on social media platforms such as Facebook, Twitter, and Instagram, where robust interactions are shaping public opinion on the boycott. In this context, this study aims to explore the impact of social media campaigns on consumer attitudes toward Israeli products in the digital era. Employing a quantitative research approach, data were gathered through surveys conducted with 100 randomly selected students in Bandung. The findings reveal that social media dissemination significantly influences cognitive, affective, and conative changes in consumer behavior. This suggests that social media campaigns play a pivotal role in shaping consumer attitudes, reflecting the complex interplay of personal values, political stances, and economic considerations. Furthermore, the study highlights the powerful role of social media in amplifying political messages, mobilizing support for social causes, and shaping perceptions on a global scale. The insights gained from this research are crucial for stakeholders, policymakers, academics, and the general public, offering a deeper understanding of how digital campaigns can drive shifts in consumer behavior within a politically charged environment.